Efficient and inefficient welfare states - Algan, Yann; Cahuc, Pierre; Sangnier, Marc (Bonn, 2011)
"This paper shows that cross country differences in the generosity and the quality of the welfare state are associated with differences in the trustworthiness of their citizens. We show that generous, transparent and efficient welfare states in Scandinavian countries are based on the civicness of their citizens. In contrast, the generosity but low transparency of the Continental European welfare states survive thanks to the support of a large share of uncivic individuals who consider that it can be justifiable to misbehave with taxes and social benefits. We also explain why countries with an intermediate degree of trustworthiness of their citizens and of transparency of the government, like Anglo-Saxon countries, have small welfare states. Overall, this paper provides a rationale for the observed persistence of both efficient and inefficient welfare states, as a function of the civicness of the citizens. "